2021
DOI: 10.3390/atmos12070815
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Early-Stage Features and Lifetime Maximum Intensity of Tropical Cyclones over the Western North Pacific

Abstract: The relationship between early-stage features and lifetime maximum intensity (LMI) of tropical cyclones (TCs) over the Western North Pacific (WNP) was investigated by ensemble machine learning methods and composite analysis in this study. By selecting key features of TCs’ vortex attributes and environmental conditions, a two-step AdaBoost model demonstrated accuracy of about 75% in distinguishing weak and strong TCs at genesis and a coefficient of determination (R2) of 0.30 for LMI estimation from the early st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Song et al (2018 studied standard deviation of LMI and found that the occurrence frequency of the strongest and weakest TCs around the world during 1999-2016 was greater than that during 1981-1998. Lu and Tang (2021) used a machine learning method to study the distribution of the LMI, which revealed that the circulation of high LMI is that lower latitude is embedded in the continuous band with high vorticity in the lower troposphere, and the circulation in the upper and lower troposphere is more dense. Recent studies have mainly focused on the characteristics of LMI in global regions or oceans, but few studies have focused on local small continental seas, such as the SCS.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al (2018 studied standard deviation of LMI and found that the occurrence frequency of the strongest and weakest TCs around the world during 1999-2016 was greater than that during 1981-1998. Lu and Tang (2021) used a machine learning method to study the distribution of the LMI, which revealed that the circulation of high LMI is that lower latitude is embedded in the continuous band with high vorticity in the lower troposphere, and the circulation in the upper and lower troposphere is more dense. Recent studies have mainly focused on the characteristics of LMI in global regions or oceans, but few studies have focused on local small continental seas, such as the SCS.…”
Section: Introductionmentioning
confidence: 99%